PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XI FASE F SMA NEGERI 8 PADANG - Hasanah, Uswatun; Elniati, Sri (Jurnal Edukasi dan Penelitian Matematika, 2024)
Proficiency in mathematical communication is crucial for students to develop, encompassing both verbal and written forms. Students' mathematical communication abilities are still rather low. The Think Pair Share cooperative learning methodology was used to address this issue. This learning paradigm has been implemented and evaluated in class XI Phase F at SMA Negeri 8 Padang. The research design is a quasi-experiment with random sampling using a Non-equivalent posttest-only control group design. A P-value of 0.005 was derived from the Mann Whitney test. Research has demonstrated that pupils utilizing the Think Pair Share cooperative learning model outperform those using traditional learning methods in class XI Phase F SMA Negeri 8 Padang.Keywords: Mathematic communication skill, Think Pair Share, Conventional Learning